Enhancing native arbuscular mycorrhizal association to improve phosphorus nutrition of rainfed upland rice (Oryza sativa L.) through cropping systems - and R.K. SINGH, D. MAITI*, M.K. BARNWAL, SULOCHANA K. RANA, M. VARIAR (Indian Phytopathology, 2006)
Efficiency of three upland rice based cropping systems in enhancing mycorrhizal population were tested in field and were compared with rice mono-cropping and the established rice + pigeon pea (Cajanus cajan L.; both annual and perennial) intercropping systems during 1998, 1999 and 2000, 2001 wet seasons. The two years’ crop rotations were (i) maize (Zea mays L.) relay cropped by horse gram (Dolichos biflorus) in the first year followed by rice sole in the second year, (ii) maize relay cropped by niger (Guizotia abyssinica L. f. Cass.) in the first year followed by rice sole in the second year and (iii) black gram (vigna mungo) sole in the first year followed by rice sole in the second year. The crop rotation involving maize relay cropped by horse gram was superior to the other systems as this system encouraged 26% more native arbuscular mycorrhizal (AM) colonization and 27% more phosphorus uptake as compared to monocropped rice in alternate years. Rice yield in two year rotation was higher by 23-29% over rice monocropping (1.1 t/ha). The total productivity of two years’ rotation (5.6 t/ha; rice equivalent), however, was comparable with rice + pigeon pea intercropping system.